2013
DOI: 10.1177/2045125313486510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active monitoring on lithium management in Norfolk

Abstract: Background: Lithium has been used in the fields of rheumatology and psychiatry since the 1800s and it is now generally considered to be a gold standard treatment for bipolar disorders. However, lithium is known to have significant side effects and requires close serum level monitoring to ensure levels remain within the therapeutic range to minimize the risk of serious adverse effects or toxicity. This article reviews the monitoring of lithium and reports on the implementation of a regional lithium register and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…For renal and thyroid tests, 73% and 60% of patients, respectively, were tested at the recommended frequency of 6 months or more often. In comparison with the most recent audits, the monitoring performance is very similar to the post-QIP POMH audit (Paton et al, 2013) and poorer than in the Norfolk audit (following the implementation of a regional lithium register and database) (Kirkham et al, 2013). Among the sub-groups at an increased risk of toxicity, there were too few patients over the age of 65 or with a chronic co-morbidity to draw meaningful conclusions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For renal and thyroid tests, 73% and 60% of patients, respectively, were tested at the recommended frequency of 6 months or more often. In comparison with the most recent audits, the monitoring performance is very similar to the post-QIP POMH audit (Paton et al, 2013) and poorer than in the Norfolk audit (following the implementation of a regional lithium register and database) (Kirkham et al, 2013). Among the sub-groups at an increased risk of toxicity, there were too few patients over the age of 65 or with a chronic co-morbidity to draw meaningful conclusions.…”
Section: Discussionmentioning
confidence: 88%
“…similar to the clozapine system). Similar strategies have previously been attempted in smaller settings (Eagles et al, 2000;Kirkham et al, 2013) and have been shown to reduce the discrepancies between guideline recommendation and clinical practice (Aubry et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Adequate monitoring of patients during lithium use is needed for early identification of patients with (potential) ADEs and for optimal dosing (Kirkham et al 2013 ; Severus et al 2008 ; Aral and Vecchio-Sadus 2008 ; Baird-Gunning et al 2017 ). So far, it is not known how different health care professionals internationally aim to achieve safe and effective lithium treatment through monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Following the introduction of the database the rates of lithium testing and monitoring have improved, helping the county to achieve national standards for the past 10 years with no known cases of toxicity due to inadequate monitoring. 8 Owing to the size of the cohort of patients on the database it is hoped that this analysis, as part of ongoing research, will establish the quantitative effect of different lithium levels on glomerular renal function expanding on work carried out by Rej et al, 9 Aiff et al 10 and Bendz et al 11 Aim and objective The aim and objective of this analysis was to establish the effects on eGFR at ≤3 months, 6 months (±3 months) and 1 year (±3 months) follow-up post exposure to a single lithium level within specified ranges, when patients are monitored in line with current UK recommendations for three monthly lithium level tests.…”
Section: Introductionmentioning
confidence: 99%
“…Following the introduction of the database the rates of lithium testing and monitoring have improved, helping the county to achieve national standards for the past 10 years with no known cases of toxicity due to inadequate monitoring. 8 Owing to the size of the cohort of patients on the database it is hoped that this analysis, as part of ongoing research, will establish the quantitative effect of different lithium levels on glomerular renal function expanding on work carried out by Rej et al , 9 Aiff et al 10 and Bendz et al . 11 …”
Section: Introductionmentioning
confidence: 99%